Metabolomics and microbial community analysis provides new insights into tea quality in different oolong tea cultivars - Yunni Chang; Zhidan Wu; Fuying Jiang; Yuzhen Chen; Jun Sun; Feng Wang (Food Chemistry: X, 2025)
Oolong tea originates from Fujian Province, and stands out for its characteristic flavor. Tea leaves microbiota and metabolites are increasingly recognized for regulating tea quality, however, the mechanism by which microorganism affect metabolites, and relationship between microorganism and metabolites remain unclear. In this study, microbiomes, metabolites and their correlation were investigated. The results showed that fungal microbiome structure changed more significantly than the bacterial one. Proteobacteria, bacteroidota, Actinobacteriota and Ascomycota were most dominant phylum, there were different key biomarker genera among different tea cultivars. Among 2017 metabolites identified in tea leaves, differential metabolites were enriched in phenylpropanoid biosynthesis and flavonoid biosynthesis. A total of 16 key common differential metabolites were selected to evaluate the relationship between metabolites and microorganism. The dominant bacterial genus most correlated with key differential metabolites were herbaspirillum, Frigoribacterium, Sphingomonas and Microbacterium. The main fungi genus correlated with differential metabolites were Phaeosphaeria, Cladosporium, Hannaella and Vishniacozyma Didymella.